2018
DOI: 10.1186/s12906-018-2095-y
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of icariin on the proliferation of neural stem cells from rat hippocampus

Abstract: BackgroundIcariin (ICA), a major ingredient of Epimediumbrevicornum, has various pharmacological activities including central nervous system protective functions such as the improvement of learning and memory function in mice models of Alzheimer’s disease. It has been reported that ICA can promote regeneration of peripheral nerve and functional recovery. The purpose of this study was to investigate the potentiating effect of ICA on the proliferation of rat hippocampal neural stem cells, and explore the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…We performed proliferation assay as previously reported that flavonoids enhance the proliferation of NSCs in an in vitro cultures [15,16]. The results of clonogenic assay revealed that in the absence of growth factors, NSCs failed to proliferate and died on the 7 th day in all tested concentrations except in Control+ve supplemented with growth factors where cells rapidly proliferated to form neurospheres at all observation time points (Fig 3).…”
Section: Trx Effects On Proliferationmentioning
confidence: 72%
See 2 more Smart Citations
“…We performed proliferation assay as previously reported that flavonoids enhance the proliferation of NSCs in an in vitro cultures [15,16]. The results of clonogenic assay revealed that in the absence of growth factors, NSCs failed to proliferate and died on the 7 th day in all tested concentrations except in Control+ve supplemented with growth factors where cells rapidly proliferated to form neurospheres at all observation time points (Fig 3).…”
Section: Trx Effects On Proliferationmentioning
confidence: 72%
“…The self-renewal capacity and the differentiation into multiple cell types of the nervous system are characteristic features which make NSCs a very useful bio-tool for the screening of molecules which exert supporting effects on neural cell proliferation [15,16,55], differentiation [19,20,22], migration [23] and synaptogenesis [45]. Flavonoids serve as effective agents which provide antioxidative protection and neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Icariin has a neuroprotective effect in both acute and chronic central nervous system disease ( Fu et al, 2018 ). In our research, it demonstrated that ICA especially at a high dose promoted motor recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Another of the neuroprotective effects of ICA is to protect neurons from the harmful effects of hyperhomocysteinaemia [18]. In addition, there are reports that Icariin improves neurogenesis and the proliferation of neuronal stem cells in the hippocampus [3,19]. It is surprising is that ICA can improve memory function by stimulating NO/ cGMP signaling and the induction of nitric oxide synthase (NOS) isoforms [20].…”
Section: Methodsmentioning
confidence: 99%